FORMING OF MECHANICAL CHARACTERISTICS OF THE SLUGS OF TITANIC ALLOY BT23 AT THERMAL TREATMENT - V. N. Fedulov (Литьë и металлургия)
Тhе changings of the initial plate structure of alloy BT23 at running of high-temperature thermal treatment of large-sized slugs with heating up to 650- 950 eC and cooling on air and in water and their influence on forming of complex of mechanical characteristics are examined.